Kung fu panda 2 - Zimmer, Hans; Powell, John, 1963- (DreamWorks Home Entertainment, 2011)
Po is now living his dream as The Dragon Warrior, protecting the Valley of Peace alongside his friends and fellow kung fu masters, The Furious Five. But Po's new life of awesomeness is threatened by the emergence of a formidable villain, who plans to use a secret, unstoppable weapon to conquer China and destroy kung fu. Po must look to his past and uncover the secrets of his mysterious origins in order to able to unlock the strength he needs to succeed.